BZR1 and BES1 transcription factors mediate brassinosteroid control over root system architecture in response to nitrogen availability - Al-Mamun, Mahamud Hossain; Cazzonelli, Christopher Ian; Krishna, Priti (Frontiers in Plant Science, 2024)
Plants modify their root system architecture (RSA) in response to nitrogen (N) deficiency. The plant steroidal hormone, brassinosteroid (BR), plays important roles in root growth and development. This study demonstrates that optimal levels of exogenous BR impact significant increases in lateral root length and numbers in Arabidopsis seedlings under mild N deficient conditions as compared to untreated seedlings. The impact of BR on RSA was stronger under mild N deficiency than under sufficient N conditions. The BR effects on RSA were mimicked in dominant mutants of BZRI and BES1 (bzr1-1D and bes1-D) transcription factors, while the RSA was highly reduced in the BR insensitive mutant bri1-6, confirming that BR signalling is essential for the development of RSA under both N sufficient and deficient conditions. Exogenous BR and constitutive activity of BZR1 and BES1 in dominant mutants, led to enhanced root meristem, meristematic cell number and cortical cell length. Under mild N deficiency, bzr1-1D displayed higher fresh and dry shoot weights, chlorophyll content and N levels in the shoot, as compared to wild type. These results indicate that BR modulates RSA under both N sufficient and deficient conditions via the transcription factors BES1/BZR1 module and confers tolerance to N deficiency.